Digital Notarial Archives in Indonesia: Regulatory Challenges vs. the EU’s GDPR Data Protection Standards - Zakiah Noer; Rizki Kurniawan (Sean Institute, 2025)
This study examines the regulatory and operational challenges faced by Indonesian notarial institutions in complying with digital data protection standards. Using a qualitative approach through legal analysis and interviews with notaries in Jakarta, Surabaya, and Bandung, the research identifies major issues, including limited understanding of data governance, lack of sector-specific regulations, and weak cybersecurity infrastructure. Although Law No. 27/2022 on Personal Data Protection provides a legal foundation, it lacks clarity and enforcement tailored to notarial functions. A comparison with the European Union’s General Data Protection Regulation (GDPR) reveals significant gaps, particularly in accountability, transparency, and risk-based mechanisms. The absence of roles such as Data Protection Officers and mandatory data impact assessments highlights the institutional unpreparedness in Indonesia. These shortcomings expose sensitive legal data to potential breaches, reducing public trust and legal reliability. The study recommends the adoption of a sector-specific regulatory model aligned with GDPR principles, supported by standardized protocols, professional training, and oversight mechanisms. These efforts are essential to ensure data security, improve institutional credibility, and support Indonesia’s transition toward secure and professional digital legal services.